THE ROLE OF SUBJECT TEACHERS IN GUIDANCE AND COUNSELING SERVICES - Lubis, Lailan Syafira Putri; Harahap, Yenni Novita; Kusyani, Diah (LUMBUNG AKSARA, 2023)
The purpose of this research is to provide a reflection of the state of cooperation between subject teachers and guidance and counseling teachers at school. In addition, it can provide subject teachers with an understanding that they have an important role in achieving the success of guidance and counseling services at school. The improvement of students' learning is not only related to what happens in the classroom; it also requires learning activities that can be applied by students in their social lives and in their future. Subject teachers need to pay attention and develop the potential of students through cooperation in the implementation of guidance and counseling service activities. The method used in this research is descriptive-qualitative, using interview, observation, and documentation techniques. The research subjects were 20 guidance and counseling teachers from 15 schools in Medan City, divided into 3 SMP, 1 Mts, 4 SMA, 5 SMK dan 2 MAS. Research results: 1.There are still many subject teachers who have not optimally carried out their duties and roles in guidance and counseling service activities; 2.There is still a lot of cooperation between guidance and counseling teachers and subject teachers around dealing with problem children. Problems that are often reported to the guidance and counseling teacher through the homeroom teacher, namely tardiness, excessive absences, skipping/dropping subjects or school hours, politeness, discipline, and quarrels. Cooperation between subject teachers and guidance and counseling teachers in student self-development, evaluation/assessment and follow-up of cases, referral of cases to the subject teacher again, case conferences and home visits still do not occur optimally.